A combined finite-element/discrete-particle analysis of a side-vent-channel-based concept for improved blast-survivability of light tactical vehicles. Issue 1 (1st February 2016) - Grujicic, Mica; Yavari, Ramin; Snipes, Jennifer; Ramaswami, S
Abstract : Purpose: – The recently proposed concept solution for improving blast-survivability of the light tactical military vehicles is critically assessed using combined finite-element/discrete-particle computational methods and tools. The purpose of this paper is to propose a concept that involves the use of side-vent-channels attached to the V-shaped vehicle underbody. Since the solution does not connect the bottom and the roof or pass through the cabin of a light tactical vehicle, this solution is not expected to: first, reduce the available cabin space; second, interfere with the vehicle occupants' ability to scout the surroundings; and third, compromise the vehicle's off-road structural durability/reliability. Furthermore, the concept solution attempts to exploit ideas and principles of operation of the so-called "pulse detonation" rocket engines in order to create a downward thrust on the targeted vehicle. Design/methodology/approach: – To maximize the downward thrust effects and minimize the extent of vehicle upward movement, standard engineering-optimization methods and tools are employed for the design of side-vent-channels. Findings: – The results obtained confirmed the beneficial effects of the side-vent-channels in reducing the blast momentum, although the extent of these effects is relatively small (3-4 percent). Originality/value: – To the authors' knowledge, the present work is the first public-domain report of the side-vent-channel blast-mitigation concept.